TUTUR ARDHASMARA ANALISIS STRUKTUR DAN SEMIOTIKA - Laksmi, Ni Luh Gede Eni (Humanis; Volume 7. No. 1. April 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Study of structure and semiotics in Tutur Ardhasmara aim for understanding the elements that built structure and semiotics, and also aim for recognizing the connote signs which is need to interpreted in order to get the precise and useful information in Tutur Ardhasmara. Theoretical used in this study is structure and semiotics theory. Structure theory used based on Teeuw; the prominent elements in a literature. For semiotics analysis is based on theory declared by Ferdinand de Saussure who analyze the meaningful signs in Tutur Ardhasmara. Method used in this study consists of three steps i.e. data collecting, data analysis and result presentation. Result of this study shows that there are exist some elements such as Prolog, Main Content, and Epilog. Prolog is preface beginning the Tutur Ardhasmara. Main content consists of Teologi and Upakara. Epilog is the end and closing part in Tutur Ardhasmara. Semiotics signs in Tutur Ardhasmara are about Sanggah Kamulan and Reinkarnasi (Reincarnation). /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Tutur, Structure, Semiotics